(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article emphasizes the importance of mathematics as a subject that plays a key role in developing students’ logical thinking, computational culture, and problem-solving skills. The educational process actively incorporates scientific approaches, innovative pedagogical technologies, and practice-oriented methods aimed at activating students’ cognitive activities, fostering independent thinking, and enhancing their creative abilities. The importance of applying modern pedagogical technologies in teaching mathematics is analyzed, including explanatory methods, practical exercises, problem-based, and interactive approaches. The effectiveness of using information and communication technologies, modular learning, the credit module system, and an integrated approach is highlighted. The article also emphasizes the significance of the teacher’s professional skills and individualized approach as factors that influence the improvement of mathematics education quality.